Aluminium‐Catalyzed C(sp)−H Borylation of Alkynes. (17th August 2021) - Willcox, Dominic R.; De Rosa, Daniel M.; Howley, Jack; Levy, Abigail; Steven, Alan; Nichol, Gary S.; Morrison, Carole A.; Cowley, Michael J.; Thomas, Stephen P.
Abstract: Historically used in stoichiometric hydroalumination chemistry, recent advances have transformed aluminium hydrides into versatile catalysts for the hydroboration of unsaturated multiple bonds. This catalytic ability is founded on the defining reactivity of aluminium hydrides with alkynes and alkenes: 1, 2‐hydroalumination of the unsaturated π‐system. This manuscript reports the aluminium hydride catalyzed dehydroborylation of terminal alkynes. A tethered intramolecular amine ligand controls reactivity at the aluminium hydride centre, switching off hydroalumination and instead enabling selective reactions at the alkyne C−H σ‐bond. Chemoselective C−H borylation was observed across a series of aryl‐ and alkyl‐substituted alkynes (21 examples). On the basis of kinetic and density functional theory studies, a mechanism in which C−H borylation proceeds by σ‐bond metathesis between pinacolborane (HBpin) and alkynyl aluminium intermediates is proposed. Abstract : The aluminium hydride catalyzed dehydroborylation of terminal alkynes is reported. By using a tethered‐intramolecular‐amine Lewis base as a ligand at the aluminium hydride centre the reactivity is controlled. Hydroalumination is switched off and selective reactions at the alkyne C−H σ‐bond are enabled.